HOW SOFT IS THE CRUST? - Ranalli G. (My University, 2003)
In a series of thermomechanical models of the lithosphere, applied to the determination of apparent elastic thickness, extension, and collision and exhumation, Burov and coworkers model the ductile behaviour of the upper crust (sometimes of the whole crust) assuming a quartz-controlled rheology.